Novel Insights into the Pathophysiology of Coronary Slow Flow Phenomenon: The Role of Triglycerides-Glucose Index and Electrocardiogram Risk Score in Subclinical Atherosclerosis - Kusuma, Singgih; Erwin Sukandi; Taufik Indrajaya; Ferry Usnizar; Irfannuddin (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: Coronary slow flow phenomenon (CSFP) is characterized by delayed distal coronary vessel opacification without significant epicardial coronary stenosis. The underlying mechanisms of CSFP remain unclear, but subclinical atherosclerosis is a likely contributor. This study investigated the relationship between the Triglycerides-Glucose Index (TyG), Electrocardiogram Risk Score (ERS), and carotid intima-media thickness (CIMT) in CSFP patients. Methods: This cross-sectional study involved 31 patients diagnosed with CSFP at Dr. Mohammad Hoesin General Hospital Palembang. CSFP was determined based on coronary blood flow slowdown on angiography. Data collection included anamnesis, physical examination, laboratory tests, echocardiography, and CIMT measurement. Statistical analysis was performed using SPSS 27. Results: The majority of CSFP patients were male (51.6%) with a mean age of 50.87 ± 13.94 years. Dyslipidemia was the most prevalent risk factor (77.4%), followed by hypertension (35.5%), smoking (22.6%), and diabetes mellitus (6.5%). Statistical analysis revealed significant positive correlations between TyG index and CIMT (r = 0.445, p = 0.012), and between ERS and CIMT (r = 0.476, p = 0.007). Conclusion: TyG and ERS indices are positively correlated with CIMT in CSFP patients. These indices may be useful tools for cardiovascular risk evaluation and early identification of high-risk patients for subclinical atherosclerosis and potential CSFP.